Illocutionary Acts of Moana’s Character Interactions in Moana Movie Dialogues - Dian nuriska Cahyanti; Nida aida; Tatu siti robiah (Lingual: Journal of Language and Culture, 2025)
The illocutionary acts found in the speech of Moana, the main character in the animated movie Moana (2016), are the focus of this investigation. Using the framework of Speech Act Theory by Searle (1979), this research aims to classify and interpret the types and functions of illocutionary utterances spoken by Moana throughout the movie. This study employs a qualitative descriptive approach, using Moana’s dialogues as the primary data, which are then examined according to the five illocutionary acts: assertive, directive, expressive, commissive, and declarative. The findings show that four types of illocutionary acts were identified: assertive (56.82%), directive (25.76%), expressive (10.61%), and commissive (6.82%), while declarative acts were not found. The dominance of assertive and directive types indicates Moana’s strong character, leadership, and assertiveness in communicating her beliefs and guiding actions. Expressive and commissive acts reflect emotional depth and responsibility. The results also reveal that illocutionary acts are vital in shaping character development, advancing the narrative, and portraying pragmatic meaning in movie dialogues. This study contributes to the field of pragmatics and can be used as an authentic source for language learning, particularly in understanding the communicative function of utterances in social and narrative contexts.